DUBLIN CORE: state of art (1995 to 2015) - Arakaki, Felipe Augusto [UNESP]; Vesu Alves, Rachel Cristina [UNESP]; Amorim da Costa Santos, Placida Leopoldina Ventura [UNESP] (Univ Federal Campina Grande, 2018)
In face of using Communication and Information Technologies in the 90 's, a new setting started to emerge as the availability of resources in Web environment. The necessity of representation, identification, location and access to resources has been widely discussed and has contributed to events and Dublin Core metadata standards. In twenty years of its creation, the Dublin Core has become a consolidated standard that has provided several possibilities for its use. However, the articles that report its history are spread out, making it difficult to gather and reconstitute them. In doing so, the aim is to show the main factors that contributed to the consolidation of the Dublin Core standard and its development. It is a qualitative and theoretical exploratory study that discusses the Dublin Core background. The outcomes identified the DC trajectory since its creation, consolidation and trends.
Keywords: Dublin Core; Historoty; Metadata